Extrahepatic portal vein obstruction in children: Role of preoperative imaging - Shashidhar Achar; Hemonta Kumar Dutta; Rudra Kanta Gogoi (Wolters Kluwer Medknow Publications, 2017)
Aim: Extrahepatic portal vein obstruction (EHPVO) is characterized by features of recent thrombosis or portal hypertension with portal cavernoma as a sequel of portal vein obstruction. Imaging of spleno-portal axis is the mainstay for the diagnosis of EHPVO. The aim of this study is to analyze the role of imaging in the preoperative assessment of the portal venous system in children with EHPVO. Materials and Methods: A hospital-based cross-sectional study was conducted on twenty children with EHPVO aged between 1 and 18 years over a period of 1 year. The children were evaluated clinically, followed by upper gastrointestinal endoscopy. Radiological assessment included imaging of the main portal vein, its right and left branches, splenic vein, and superior mesenteric vein using color Doppler ultrasonography (CDUSG) and magnetic resonance portovenogram (MRP). Evidence of portal biliopathy, status of collaterals, and possible sites for portosystemic shunt surgery were also examined. Results: All the patients presented in chronic stage with portal cavernoma and only one patient (5%) had bland thrombus associated with cavernoma. The CDUSG and MRPs had a sensitivity of 66.6-90% and 96.7% and specificity of 91.5% and 98.3% respectively with regard to the assessment of the extent of thrombus formation and flow in the portal venous system. Both the modalities were found to be complementary to each other in preoperative assessment of EHPVO. However, the sensitivity of MRP was slightly superior to CDUSG in detecting occlusion and identifying portosystemic collaterals and dilated intrahepatic biliary radicals. Conclusion: Results of the present study indicate that MRP is well suited and superior to CDUSG in the preoperative imaging of patients with EHPVO.